Responses of grazing households to different levels of payments for ecosystem services. Issue 1 (31st December 2022) - Shen, Weiwei; Zhou, Ting; Chang, Hong; Qiu, Xiao; Liu, Yahong; Sun, Hailian; Zhai, Xiu; Yang, Hongbo; Liu, Guihuan; Yang, Wu
ABSTRACT: Introduction: Payments for Ecosystem Services (PES) programs have been implemented globally to protect ecosystems while securing the well-being of affected people. Reasonable payment standards are key to successful PES programs. Although some approaches are available for determining payment standards, few studies have applied them for grassland conservation with location indicators and socioeconomic contexts properly considered. Methods: Using China's first pilot Grassland Ecological Compensation Policy (GECP) as an example, we analyzed the effects of payment levels, other natural and socioeconomic factors on herders' willingness to participate in the GECP in Damao County in Inner Mongolia where grassland degradation is happening at an alarming rate due to overgrazing and cropland expansion. Outcomes: Our results show that households with lower herding income, older age, higher education, larger grassland areas, and worse social relationships are more inclined to participate in the GECP. Conservation payment level, as well as natural and socioeconomic contextual factors, significantly affect the response of herdsmen, and a reasonable grassland payment standard with a 95% policy compliance rate should be 8.8 yuan mu −1 . Discussion and Conclusion: Our findings can inform governments to develop effective PES programs to balance the need of human well-being improvement and grassland conservation in China and beyond.